Investigation Factors Affecting Elderly Awareness of Smoking Stopping - Helprida Sihite; Sari Siregar; Nova Sontry Node Siregar; Debora N Simamora; Fransiska Debataraja (Sean Institute, 2023)
Smoking behavior remains a global health issue due to its connection to various diseases and even death. Understanding the factors influencing elderly awareness to quit smoking is crucial for public health interventions. A study conducted in Bonan Dolok I Village, Sijamapolang District, Humbang Hasundutan Regency, aimed to analyze factors affecting the elderly's awareness to quit smoking. The factors explored included knowledge, sources of information, age, work, and family support. The study used a cross-sectional design with an analytic descriptive quantitative approach and involved 41 elderly men in the village. The results showed that 85.4% of the participants had good knowledge, 87.8% had a good source of information, 87.8% had good family support, and 90.2% were aged between 60 and 79 years. The Chi-Square test revealed no significant relationship between knowledge factors, sources of information, family support, age, occupation, and elderly awareness to stop smoking (P> 0.05). Based on these findings, the study concluded that factors such as knowledge, sources of information, family support, age, and work do not significantly affect the awareness of the elderly to stop smoking in the village of Bonan Dolok I. It is recommended for further research to consider other factors such as personal motivation, mental health, and social influence in designing interventions to increase awareness of stopping smoking in the elderly population